2022
DOI: 10.1007/s40266-022-00933-2
|View full text |Cite
|
Sign up to set email alerts
|

Management of Advanced Urothelial Carcinoma in Older and Frail Patients: Have Novel Treatment Approaches Improved Their Care?

Abstract: Patients with urothelial carcinoma (UC) tend to be older and frailer with a large number of chronic medical conditions. This is particularly pronounced in those with locally advanced or metastatic UC. Prior to 2016, treatment options in advanced urothelial carcinoma (aUC) were limited to chemotherapy, and as a result, a large number of patients were not receiving diseasedirected therapy. Over the last six years, multiple alternative modalities including immune checkpoint inhibitors, enfortumab vedotin, sacituz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 106 publications
0
3
0
Order By: Relevance
“…[102][103][104] Previous studies indicated that age does not affect the efficacy and tolerance of ICIs if patients are fit enough to receive therapy. 105 Advanced cancer patients older than 65 years may suffer from more underlying diseases and accept more concomitant medication than those younger than 65 years, resulting in shorter OS and PFS. 106,107 Our results show that only patients older than 65 years have a better response to ICIs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[102][103][104] Previous studies indicated that age does not affect the efficacy and tolerance of ICIs if patients are fit enough to receive therapy. 105 Advanced cancer patients older than 65 years may suffer from more underlying diseases and accept more concomitant medication than those younger than 65 years, resulting in shorter OS and PFS. 106,107 Our results show that only patients older than 65 years have a better response to ICIs.…”
Section: Discussionmentioning
confidence: 99%
“…In the age subgroup, patients older than 65 years had a higher risk of progression and death than those younger than 65 years, which may be attributed to age-associated decline in immune function, known as immunosenescence or age-related immune dysfunction 102–104. Previous studies indicated that age does not affect the efficacy and tolerance of ICIs if patients are fit enough to receive therapy 105. Advanced cancer patients older than 65 years may suffer from more underlying diseases and accept more concomitant medication than those younger than 65 years, resulting in shorter OS and PFS 106,107.…”
Section: Discussionmentioning
confidence: 99%
“…Treatment decision-making for older patients with mUTC is complex and driven by multiple factors, such as patient preference, physician’s assessment for treatment tolerability, and patient frailty [ 27 ]. Though age may be associated with increased frailty and treatment toxicity, it does not constitute a reliable prognostic factor [ 28 ]. Our study showed that older patients had comparable outcomes to their younger counterparts regardless of the systemic treatment received.…”
Section: Discussionmentioning
confidence: 99%